2013
DOI: 10.4103/0971-4065.111845
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 271 arteriovenous fistulas as vascular access for hemodialysis

Abstract: This report describes our experience of arteriovenous fistula (AVF) creation as vascular access for hemodialysis (HD). Study has been carried out in Deenanath Mangeshkar Hospital, Pune from January 2004 to December 2009. A total of 271 AVFs were created in 249 patients. Maximum follow up was 7 years and minimum was 1 year. In this study of 271 cases of AVFs, there were 196 (72.3%) successful cases and 75 (27.7%) failures. Basilic vein was used in 77 (28.4%) cases, cephalic vein in 186 (68.6%), and antecubital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 10 publications
2
31
1
5
Order By: Relevance
“…A majority of patients in this study were males (76%). This finding is consistent with that reported by Sahasrabudhe et al 5 and Sahin et al1. They reported that there were 65.7% and 62.07% males in their study respectively.…”
Section: Post-operativesupporting
confidence: 94%
“…A majority of patients in this study were males (76%). This finding is consistent with that reported by Sahasrabudhe et al 5 and Sahin et al1. They reported that there were 65.7% and 62.07% males in their study respectively.…”
Section: Post-operativesupporting
confidence: 94%
“…American Institute of Ultrasound in Medicine Practice Guideline revised in 2011 states that the lumen diameter of artery below 2 mm and vein diameter below 2.5 mm lead to higher failure rates [6]. We think that colored Doppler ultrasound is not so helpful in evaluating the vessels in the arm, from our previous experiences.…”
Section: Discussionmentioning
confidence: 91%
“…15 In another study, majority of patients with AVF had steal phenomenon and distal edema. 13 Another study reported most common complication in patient with AVF was thrombosis (30.5%). 6 Another study reported data of 96 patients with 104 femoral catheters used for 1 to 26 days.…”
Section: Discussionmentioning
confidence: 97%
“…Eighty-one fistulas were constructed on right side and 190 were on left side. 13 One eighty-seven patients had AVF on radial artery and 84 had AVF on brachial artery. 13 In general, when AFS are planned, non-dominant limb preferred, for example, if the patient is right-handed, left arm is preferred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation